2020
DOI: 10.1111/jipb.12888
|View full text |Cite
|
Sign up to set email alerts
|

A WRKY transcription factor confers aluminum tolerance via regulation of cell wall modifying genes

Abstract: Modification of cell wall properties has been considered as one of the determinants that confer aluminum (Al) tolerance in plants, while how cell wall modifying processes are regulated remains elusive. Here, we present a WRKY transcription factor WRKY47 involved in Al tolerance and root growth. Lack of WRKY47 significantly reduces, while overexpression of it increases Al tolerance. We show that lack of WRKY47 substantially affects subcellular Al distribution in the root, with Al content decreased in apoplast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…Due to its negatively charged carboxylic groups, the pectic matrix is generally considered to be the major Al binding site of the cell wall, resulting in toxicity (Blamey et al, 1990;Chang et al, 1999;Horst et al, 2010). Nevertheless, recent studies have demonstrated that hemicellulose contributes significantly to Al accumulation and Al-induced root growth inhibition in Arabidopsis thaliana (Yang et al, 2011;Zhu et al, 2012;Li et al, 2020). Arabidopsis hemicellulose is mainly composed of non-charged xyloglucan, which has been proposed to be the principal binding site for Al, although the structural features of xyloglucan required for the binding of Al are still unclear (Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its negatively charged carboxylic groups, the pectic matrix is generally considered to be the major Al binding site of the cell wall, resulting in toxicity (Blamey et al, 1990;Chang et al, 1999;Horst et al, 2010). Nevertheless, recent studies have demonstrated that hemicellulose contributes significantly to Al accumulation and Al-induced root growth inhibition in Arabidopsis thaliana (Yang et al, 2011;Zhu et al, 2012;Li et al, 2020). Arabidopsis hemicellulose is mainly composed of non-charged xyloglucan, which has been proposed to be the principal binding site for Al, although the structural features of xyloglucan required for the binding of Al are still unclear (Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although it sequence had high similarities to AetWRKY6, TaWRKY, and TaWRKY5 in Triticum or OsWRKY30 in rice, their functions in responses to metal stresses have not been identi ed. Similar to other plant WRKY transcription factors (32,33,36,39), TaWRKY74 was more markedly induced by Cu stress compare to Al and Cd stress ( Fig. 5), suggesting that the TaWRKY74 transcription factor plays more key roles in the response to Cu stress in wheat.…”
Section: Discussionmentioning
confidence: 57%
“…The WRKY transcription factors, the largest families of plants transcription factors, have been reported to play crucial roles by regulating the downstream target gene expression in response to various metal stresses. Under Al stress, for instance, OsWRKY22 in rice, WRKY46 and WRKY47 in Arabidopsis, were participated in Al tolerance by regulating the related genes expression [32,33,39]. Additionally, ZmWRKY4 in Zea mays, WRKY53 in Thlaspi caerulescens, ThWRKY7 in Tamarix hispida, and WRKY12 and WRKY13 in Arabidopsis have been reported to respond to Cd stress via different pathways [35,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, HvHOX9, a novel homeobox-leucine zipper transcription factor, was identified to play a critical role in Al tolerance in barley by decreasing root CW Al binding, increasing apoplastic pH in the root, and silencing of HvHOX9 which increased Al accumulation in root CW and decreased H + influx after Al exposure [136]. Li et al showed that WRKY47 was involved in altering Al distribution between the apoplast and symplast by regulating the genes responsible for CW modification, thereby improving Al tolerance [125]. Lou et al reported that a NAC-type TF, VuNAR1, is involved in Al resistance in rice beans, and overexpression of VuNAR1 induced higher WAK1 expression and low pectin content via directly binding to the WAK1 promoter and regulating CW pectin metabolism [138].…”
Section: Transcription Factors Are Involved In Adaptation To Al Stressmentioning
confidence: 99%